2022
DOI: 10.1101/2022.06.02.494606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actin nucleotide state modulates the F-actin structural landscape evoked by bending forces

Abstract: ATP hydrolysis-coupled actin polymerization is a fundamental mechanism of cellular force generation. Force and actin filament (F-actin) nucleotide state in turn modulate the engagement of actin binding proteins (ABPs) to regulate actin dynamics through unknown mechanisms. Here, we show that bending forces evoke structural transitions in F-actin which are modulated by actin nucleotide state. Cryo-electron microscopy (cryo-EM) structures of ADP- and ADP-Pi-F-actin with sufficient resolution to visualize bound so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…By contrast, our structures are remarkably similar in all solved nucleotide states, showing that ADP-F-actin should not be regarded as destabilized but rather as a 'primed state', which exhibits faster depolymerization rates at the filament ends and is sensitive to cofilin binding and severing due to the absence of the γ-phosphate moiety. This model is highly consistent with a recent study, which showed that the nucleotide state affects the bending and mechanical properties of the filament, rather than large amino-acid rearrangements 46 . We furthermore show how the mechanism of ATP hydrolysis in F-actin and the slow polymerization rates of Ca 2+ -actin depend on the positions of water molecules, emphasizing that high-resolution structures are crucial for explaining these important aspects of filament assembly and aging.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, our structures are remarkably similar in all solved nucleotide states, showing that ADP-F-actin should not be regarded as destabilized but rather as a 'primed state', which exhibits faster depolymerization rates at the filament ends and is sensitive to cofilin binding and severing due to the absence of the γ-phosphate moiety. This model is highly consistent with a recent study, which showed that the nucleotide state affects the bending and mechanical properties of the filament, rather than large amino-acid rearrangements 46 . We furthermore show how the mechanism of ATP hydrolysis in F-actin and the slow polymerization rates of Ca 2+ -actin depend on the positions of water molecules, emphasizing that high-resolution structures are crucial for explaining these important aspects of filament assembly and aging.…”
Section: Discussionsupporting
confidence: 91%
“…Myosin motors are also potentially suitable as force-generators compatible with cryo-EM experiments, although their stochasticity will inevitably introduce heterogeneity which is refractory to high-resolution structure determination. Nevertheless, continuous progress in classification algorithms, particularly the recent introduction of approaches for handling continuous structural variability [104,105], which were successfully employed to characterize F-actin bending [103], may render this approach tractable.…”
Section: Potential Structural Mechanisms For Forceactivated Actin Bin...mentioning
confidence: 99%
“…Fluid forces exerted by blotting and surface tension in thin films associated with the preparation of cryo‐EM specimens have been suggested to impact F‐actin structure [12], and it may be possible to productively harness these forces experimentally. Indeed, our lab has very recently used single‐particle cryo‐EM to interrogate F‐actin structural transitions evoked by bending forces under such standard conditions [103]. By developing a machine learning‐based particle picking approach, we detected and characterized bent filament segments featuring a continuous range of curvatures up to 8 μm −1 [103].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, structural data on F-form actin has been more challenging to obtain. During the last years, advances in single-particle electron cryo-microscopy (cryo-EM) have enabled determining high-resolution structures of F-actin from different organisms, such as skeletal muscle α-actin from Mus musculus [13], Oryctolagus cuniculus [14], Gallus gallus [15][16][17], Leishmania major [18] and actin I from P. falciparum [19] to resolutions between 2.15-3 Å. The short length and instability of P. falciparum actin I has allowed structure determination only of filaments stabilized by jasplakinolide (JAS).…”
Section: Introductionmentioning
confidence: 99%